2021
DOI: 10.1186/s12967-021-02882-7
|View full text |Cite
|
Sign up to set email alerts
|

The fecal microbiota of patients with pancreatic ductal adenocarcinoma and autoimmune pancreatitis characterized by metagenomic sequencing

Abstract: Background The fecal microbiota in pancreatic ductal adenocarcinoma (PDAC) and in autoimmune pancreatitis (AIP) patients remains largely unknown. We aimed to characterize the fecal microbiota in patients with PDAC and AIP, and explore the possibility of fecal microbial biomarkers for distinguishing PDAC and AIP. Methods 32 patients with PDAC, 32 patients with AIP and 32 age- and sex-matched healthy controls (HC) were recruited and the fecal microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 43 publications
1
55
0
Order By: Relevance
“…Histone acetylation and deacetylation have been revealed as important factors for the regulation of cancer progression [ 42 ]. Studies have shown that abnormal histone deacetylation is associated with malignant tumors and HDACi can inhibit cancer progression through remodeling histone acetylation [ 43 ]. Until recently, the inhibitory effect of HDAC1 has been proved in different types of cancer cells, including breast cancer, gastric cancer, pancreatic cancer, non-small cell lung cancer, and colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Histone acetylation and deacetylation have been revealed as important factors for the regulation of cancer progression [ 42 ]. Studies have shown that abnormal histone deacetylation is associated with malignant tumors and HDACi can inhibit cancer progression through remodeling histone acetylation [ 43 ]. Until recently, the inhibitory effect of HDAC1 has been proved in different types of cancer cells, including breast cancer, gastric cancer, pancreatic cancer, non-small cell lung cancer, and colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Some microbes are more abundant in Pancreatic Ductal Adeno Carcinoma (PDAC) patients including Klebsiella pneumoniae, Clostridium bolteae, S. mutans, and Parabacteroides spp., Acinetobacter, and Pseudomonas (Thomas and Jobin, 2020;Lau et al, 2021;Matsukawa et al, 2021). The abundance of other microbes such as Firmicutes is significantly lower in PDAC patients (Lau et al, 2021;Zhou et al, 2021). Most PDAC patients suffer from a leaky gut which results in the translocation of harmful bacteria into the bloodstream (Wu et al, 2014).…”
Section: Microbiome Implications In the Development Of Malignant Tumorsmentioning
confidence: 99%
“…The microbiota could also play a role as a potential biomarker in the differential diagnosis of pathologies that can mimic PDAC, such as autoimmune pancreatitis [78]. When analyzing the microbiota of patients with adenocarcinoma and autoimmune pancreatitis, Zhou et al found a significant difference in bacterial types and fecal butyrate content [79]. In patients with PDAC, there was a large decrease in Firmicutes (mainly butyrate-producing bacteria), and an increase in Proteobacteria (mainly Gammaproteobacteria).…”
Section: Gut Microbiota and Intratumor Microbiota In Pdacmentioning
confidence: 99%